(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
The aim of this paper is analyzing the archaeological fea- tures, place and personal names of central Portugal in mid 1st millennium BC to try to assess the arrival of a Tartessian population to the area. This fact is suggested by the presence of the -ipo place names, well known in South- western Iberia; the mortuary practices of the necropolis of Alcácer do Sal, very similar to those ones of the necropoleis of Medellín and Cruz del Negro and some pottery features such as the Paleohispanic writing graffiti and the Burnished Grey ware pottery, well attested also in Medellín and Southwestern Iberia. Besides it is analysed pthe process and structure of this Tartessian colonization from the Lower Gauadalquivir valley to Guadiana valley and the mouths of the Tagus and Sado rivers.